A Water‐Soluble Mn(CO)3‐Based and Non‐Toxic PhotoCORM for Administration of Carbon Monoxide Inside of Cells. Issue 23 (10th November 2017) - Mede, Ralf; Hoffmann, Patrick; Klein, Moritz; Görls, Helmar; Schmitt, Michael; Neugebauer, Ute; Gessner, Guido; Heinemann, Stefan H.; Popp, Jürgen; Westerhausen, Matthias
Abstract : The photoCORMs [Mn(CO)3 (L)]Br with the tridentate ligands L1 = S[(CH2 )2 NH2 ]2 (1 ) (CORM‐EDE3) and L2 = cyclo ‐S[(CH2 )2 NH(CH2 ‐)]2 (2 ) (CORM‐EDE4) are non‐toxic and release all CO ligands upon irradiation. Reduction of the hydrophilicity of the cation by L2 (thia‐4, 7‐diazacyclononane) enables accumulation of the resulting water‐soluble CORM‐EDE4 as well as administration of CO inside of cells. Abstract :